PMT family mannosyltransferase-mediated protein O-mannosylation is required for the development and pathogenicity of Colletotrichum graminicola - Jie Mei; Na Ning; Yan Yang; Shaoqun Zhou; Wende Liu (Phytopathology Research)
Abstract Protein O-mannosylation in the endoplasmic reticulum (ER) plays a crucial regulatory role in the development and virulence of many phytopathogenic fungi. However, the corresponding biological function and underlying regulatory mechanism mediated by this process in Colletotrichum graminicola, causing the anthracnose disease of maize (Zea mays), is unclear. The protein O-mannosyltransferase (PMT) family-mediated protein O-mannosylation is absent in plants, which may provide good targets for developing safe antifungal agents. In the present study, we identified three PMT family mannosyltransferases: CgPMT1, CgPMT2, and CgPMT4 in C. graminicola. The subcellular localization analyses proved that these proteins were located in the ER as previously reported. qRT-PCR results showed that the expression levels of all the three genes were highest in the conidia compared with other developmental stages. Gene knockout analysis demonstrated that the PMT-mediated protein O-mannosylation was essential for the vegetative growth, conidiation, appressorium formation, and pathogenicity of C. graminicola. Immunoprecipitation-Mass Spectrometry (IP-MS) analysis showed that the potential interaction proteins of these CgPMTs were mainly enriched in the pathways of sphingolipid metabolism, autophagy, glycosylphosphatidylinositol (GPI)-anchor modification, and endocytosis. These findings enhanced our understanding of the functions of protein O-mannosylation and provide effective molecular targets for maize disease prevention and control.